MENINGKATKAN KINERJA GURU DENGAN PENDEKATAN DIREKTIF - Agung Purwanto (JURNAL GLOBAL EDUKASI, 2019)
Abstract: Identification of problems that occur in Tapung Hilir 4 Public Middle School are as follows, specifically related to teachers: the small number of teachers who compose the learning outcomes test grid both independently and collaboratively, there are still many teachers who choose shortcuts to compile test results through copy paste, so that mistakes often occur, for example multiple questions, writing questions is not in accordance with the rules of writing the results of the study. Through this research, researchers used the workshop activities with a directive approach to improve the quality of learning outcomes tests and in accordance with the rules of writing questions and tests in accordance with Subject Competency Basics. The study was conducted in two cycles with the duration of the meeting as many as 4 meetings. This research was conducted for 3 months, July to September 2018 which was held at Tapung Hilir 4 Public Middle School. After a workshop with a directive approach in preparing the learning outcomes test each cycle has increased. Work cycle I behavior with good (3) and very good categories (4) in cycle I 49.45% increased in cycle II 97.80%. For the value of the results of the performance in compiling the grid test the learning outcomes of the first cycle 30.77% increased in the second cycle 84.62%. Keywords: Teacher Behavior and Performance, Directive Approach Abstrak: Identifikasi masalah yang terjadi di SMP Negeri 4 Tapung Hilir diantaranya sebagai berikut, khusus yang berhubungan dengan guru : sedikitnya jumlah guru yang menyusun kisi-kisi tes hasil belajar baik secara mandiri maupun berkolaborasi, masih banyak guru memilih jalan pintas untuk menyusun tes hasil belajar melalui copy paste, sehingga sering terjadi kesalahan-kesalahan, misalnya soal ganda, penulisan soal tidak sesuai dengan kaidah penulisan tes hasil belajar. Melalui penelitian ini peneliti menggunakan tindakan kegiatan workshop dengan pendekatan direktif untuk meningkatkan mutu tes hasil belajar dan sesuai dengan kaidah penulisan soal serta tes sesuai dengan Kompetensi Dasar Mata Pelajaran. Penelitian dilaksanakan dua siklus dengan durasi pertemuan sebanyak 4 kali pertemuan. Penelitian ini dilaksanakan selama 3 bulan, Juli sampai dengan September 2018 yang dilaksanakan pada SMP Negeri 4 Tapung Hilir. Setelah dilakukan workshop dengan pendekatan direktif dalam menyusun tes hasil belajar setiap siklusnya mengalami peningkatan. Perilaku kerja siklus I dengan kategori baik (3) dan sangat baik (4) pada siklus I 49,45% meningkat pada siklus II 97,80%. Untuk nilai hasil kinerja dalam menyusun kisi-kisi tes hasil belajar siklus I 30,77% meningkat pada siklus II 84,62%. Kata kunci: Perilaku dan Kinerja Guru, Pendekatan Direktif